2018
DOI: 10.1093/mmy/myx156
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effect of Saccharomyces cerevisiae KTP and Issatchenkia occidentalis ApC on hyphal development and adhesion of Candida albicans

Abstract: The morphological transition from yeast to a hyphal form, as well as the adhesion capability to the gastrointestinal tract, are implicated virulent determinant in Candida albicans and could be potential targets for prevention of the opportunistic pathogen. Based on this rationale, two yeast strains Saccharomyces cerevisiae KTP and Issatchenkia occidentalis ApC along with reference strain Saccharomyces boulardii NCDC 363 were screened for the probiotic potential. Characters like pH, temperature, bile, simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…occidentalis (strain ApC; accession no. KF551991) from toddy and apple cider, respectively (22). Here, we tested the probiotic potential of these yeasts against non- albicans Candida species C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…occidentalis (strain ApC; accession no. KF551991) from toddy and apple cider, respectively (22). Here, we tested the probiotic potential of these yeasts against non- albicans Candida species C.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is limited knowledge about the effects of probiotic yeasts on non- albicans Candida strains. Here, we tested the effects of two novel probiotic yeasts, Saccharomyces cerevisiae (strain KTP) and Issatchenkia occidentalis (strain ApC), that were derived from food sources (22). Here, we used multiple readouts, including in vitro and ex vivo assays and analyses of morphological transition and biofilm formation of four non- albicans Candida strains, C.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have observed that beneficial yeast action is dose dependent, where cell density (10 8 /ml) plays a key role in adhesion and hyphal inhibitory ability of Candida species ( 14 , 23 ). Furthermore, heat-killed beneficial yeasts were largely ineffective ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…We and others have observed that beneficial yeast action is dose dependent, where cell number (10 8 / ml) plays a key role in adhesion and hyphal inhibitory ability of Candida species (Lohith andAnu-Appaiah, 2018, Kunyeit et al, 2019). Furthermore, heat-killed beneficial yeasts were largely non-functional (Figure supplement 7).…”
Section: Secretome Of Beneficial Yeast Confer Protective Activitymentioning
confidence: 93%